Community-Based Mental Health Care in Britain - Tom Burns (Eco-Vector, 2020)
Community mental health care in the UK was established by two influential mental health acts (MHAs). The 1930 MHA legislated for voluntary admissions and outpatient clinics. The 1959 MHA required hospitals to provide local follow- up after discharge, required them to work closely with local social services and obliged social services to help with accommodation and support. An effect of this was to establish highly sectorized services for populations of about 50,000. These were served by multidisciplinary teams (generic CMHTs), which accepted all local referrals from family doctors. Sector CMHTs evolved a pragmatic approach with an emphasis on skill-sharing and outreach, depending heavily on community psychiatric nurses. The NHS is funded by central taxation, with no distortion of clinical practice by per-item service fees. It is highly centrally regulated, with a strong emphasis on evidence-based treatments.